2022
DOI: 10.3390/agronomy12010124
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bacterial and Fungal Community of Soil under Treatment of Pesticides

Abstract: Experiments were carried out in soil microcosms with the treatment of pesticide formulations—imidacloprid, benomyl, and metribuzin in single and tenfold application rates. For additional stimulation of microorganisms, a starch–mineral mixture was added to some variants. For all samples, high-throughput sequencing on the Illumina MiSeq platform of the V4 (16S rRNA) and ITS1 (18S rRNA) fragments was carried out. As a result, it was possible to establish the characteristic changes in the structure of the soil fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…We also found that research on the effects of neonicotinoids on soil microorganisms has produced conflicting results. Some studies did not find any adverse effects of neonicotinoids on microorganisms (Garg et al, 2021;Li et al, 2018;Parizadeh et al, 2021;Singh & Singh, 2005a;Zhang et al, 2015), while some found significant changes in the microbial community in terms of relative abundance (Garg et al, 2021;Parizadeh et al, 2021;Streletskii et al, 2022;Wu et al, 2021;Zhang et al, 2018), diversity and structure (Cai et al, 2015;Wu et al, 2021;Yamaguchi et al, 2021;Yu et al, 2020;Zhang et al, 2015;Zhang et al, 2018;Zhang et al, 2021) and enzymatic activity (Cai et al, 2016a;Castillo Diaz et al, 2017;Filimon et al, 2015;Wang et al, 2014). Such contradictory results may be because some authors investigated only eukaryotes, some only prokaryotes, and others a combination of the two groups.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We also found that research on the effects of neonicotinoids on soil microorganisms has produced conflicting results. Some studies did not find any adverse effects of neonicotinoids on microorganisms (Garg et al, 2021;Li et al, 2018;Parizadeh et al, 2021;Singh & Singh, 2005a;Zhang et al, 2015), while some found significant changes in the microbial community in terms of relative abundance (Garg et al, 2021;Parizadeh et al, 2021;Streletskii et al, 2022;Wu et al, 2021;Zhang et al, 2018), diversity and structure (Cai et al, 2015;Wu et al, 2021;Yamaguchi et al, 2021;Yu et al, 2020;Zhang et al, 2015;Zhang et al, 2018;Zhang et al, 2021) and enzymatic activity (Cai et al, 2016a;Castillo Diaz et al, 2017;Filimon et al, 2015;Wang et al, 2014). Such contradictory results may be because some authors investigated only eukaryotes, some only prokaryotes, and others a combination of the two groups.…”
Section: Discussionmentioning
confidence: 98%
“…Neonicotinoid exposure studies that reported adverse effects on soil microbial populations Thirteen studies (45%) discussed the adverse effect of neonicotinoids (clothianidin, dinotefuran, imidacloprid, paichongding, thiacloprid and thiamethoxam) on soil microbial relative abundance, diversity, activity, community composition and community structure. Imidacloprid changed the relative abundance of some eukaryotic genera named Apiotrichum, Gamsia, Humicola, Kitasatospora, Solicoccozyma and prokaryotic genera named Sphingomonas, Streptomyces and Terrabacter (Streletskii et al, 2022). In comparison to bacteria, low relative abundances of the archaea genera Crenarchaeota and Euryarchaeota were found in loam and clay loam soil treated with imidacloprid, thiacloprid and clothianidin (Zhang et al, 2018).…”
Section: Neonicotinoid Studies That Reported No Adverse Effect On The...mentioning
confidence: 97%
“…Their study further confirmed the drop in fungal biomass with increasing pesticide concentration. These alterations in soil fungal diversity and counts with the application of pesticides is further confirmed by Streletskii et al (2022). A concentration of 1 μl/100 ml paraquat dichloride produced reduced abundance in Aspergillus niger with a 34 mm zone of inhibition in agar diffusion studies (Geetha et al 2016) while the insecticide, endosulfan at 100 g/L hampered the growth of Aspergillus terrus and Clasdosporium oxysporum (Mukherjee & Mittal, 2005).…”
Section: Discussionmentioning
confidence: 87%
“…Several species of this genus are thermophilic fungi, which can break down complex natural substrates [ 46 ]. With the treatment of pesticide formulations—imidacloprid, benomyl, andmetribuzin, the relative abundance of the genera Humicola changed [ 51 ]. Previous studies have confirmed that pathogens within the Fusarium genus are the primary agents of Fusarium head blight (FHB) of wheat, which causes yield reduction and deoxynivalenol contamination, attracting immense concern worldwide [ 47 ].…”
Section: Discussionmentioning
confidence: 99%